The effect of blood glucose levels on serum triglyceride clearance in patients with hyperlipidemic acute pancreatitis - Yuxin Liu; Shuqi Qin; Si Dai; Jing Zhou; Zhendan Wang; Guojian Yin (Scientific Reports)
Abstract Preventing moderately severe and severe acute pancreatitis (MSAP & SAP) is the primary goal of the management of hyperlipidemic acute pancreatitis (HLAP). The main aim of this study was to investigate the factors affecting serum triglyceride (TG) clearance, particularly blood glucose (GLU) levels, which could potentially help to prevent the development of MSAP & SAP. The clinical data from 177 patients with MSAP & SAP and 195 patients with mild acute pancreatitis (MAP) on days 1–6 after the onset were collected and analyzed by multivariate logistic regression to identify the factors that have an impact on the severity of HLAP, especially TG. The optimal TG threshold was obtained by receiver operating characteristic (ROC) analysis to differentiate TG fast-clearance patients from TG slow-clearance patients, as defined in this study. Metabolism-related factors that may interfere with TG clearance, such as GLU, diabetes mellitus (DM), obesity, and uric acid, were further analyzed. Day 2 TG was an independent risk factor for MSAP & SAP in patients with HLAP (OR: 3.718, 95% CI: 2.042–6.77; P < 0.001). And patients with TG slow-clearance (day 2 TG ≥ 7.335 mmol/L) were more likely to develop MSAP & SAP (sensitivity 0.932, specificity 0.898), severe pancreatic necrosis, and death. DM (OR: 3.574, 95% CI: 1.13–11.308, P < 0.001) and day 2 GLU (OR: 1.537, 95% CI: 1.292–1.675; P < 0.001) were independent risk factors for TG slow-clearance but not for HLAP severity (OR: 1.728, P = 0.253 and OR: 1.119, P = 0.059). Day 2 GLU decreased below 13.07 mmol/L and 6.575 mmol/L in patients with DM and non-diabetes mellitus (NDM), respectively, contributing to the reduction of day 2 TG to 7.335 mmol/L. Day 2 TG levels had the most impact on the severity of HLAP, which also accurately predicted the occurrence of MSAP & SAP. It is worth noting whether the GLU can reach the target value on day 2, as it can directly affect the TG clearance rate and indirectly affect the severity of HLAP.